Boarding School System in Forming the Discipline Character of Worship at MTsN 1 Bengkulu City - Lestari Nengsih; Alimni (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Madrasah boarding schools have a very potential strategic position, not only as living areas and study areas but also as social interaction areas that can support the positive personality development of their residents. The pattern of education and parenting in dormitories is very much needed to support the development of students' individuality with media internalization and actualization of religion and religious values, therefore, the management of education in dormitories is essential for optimizing the success of the madrasah program. The focus of this research is to discuss the influence of the boarding school system in shaping the character of the discipline of worship at the MTsN 1 Dormitory in Bengkulu City. This research is a field research, using descriptive qualitative method. The research data were obtained from observations, interviews with dormitory heads, administrators, and dormitory students. The results of this study concluded that the application of the boarding madrasa system in shaping the character of religious discipline at MTsN 1 Bengkulu City includes prayer education (fardlu and sunnah), remembrance, and recitations of the al-Qu'an. The implementation of worship education is listed in the daily program (rules of conduct), which, if violated, will be subject to sanctions. Religious education is carried out with continuous habituation. From the results of implementing the rules, students can carry out worship in an orderly manner according to a predetermined program